A preliminary checklist of the millipedes (Diplopoda) of the Great Smoky Mountains National Park, USA - Snyder, Bruce A. (Zootaxa, 2008)
Great Smoky Mountains National Park, the most visited National Park in the United States, is home to a wide diversity of millipede species. A preliminary list of these species is provided, based on literature records and new collections from the All-Taxa Biodiversity Inventory and the author’s research. This report establishes that the Park’s presently known fauna consists of 62 species (one of which contains two subspecies) in 21 families and all 10 orders known from eastern North America, and includes at least five new state records and 18 new Park records. In the near future several undescribed species will likely be added to the list, as well as described species that are currently known to occur near the Park, but have never been reported from within the Park’s boundary.Key words: Appalachian Mountains, ATBI, North Carolina, Tennessee, biodiversity, inventory, GSMNP